2009
DOI: 10.1002/gcc.20694
|View full text |Cite
|
Sign up to set email alerts
|

Are there any more ovarian tumor suppressor genes? A new perspective using ultra high‐resolution copy number and loss of heterozygosity analysis

Abstract: Ovarian cancer is characterized by complex genetic alterations, including copy number loss and copy number-neutral loss of heterozygosity (LOH). These alterations are assumed to represent the "second hit" of the underlying tumor suppressor gene (TSG), however, relative to the number of LOH hotspots reported, few ovarian TSGs have been identified. We conducted a high-resolution LOH analysis using SNP arrays (500K and SNP6.0) of 106 primary ovarian tumors of various histological subtypes together with matching n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 29 publications
4
55
0
Order By: Relevance
“…Among those altered genes, IQGAP2 is hypermethylated and its expression is decreased in ovarian cancers. Indeed, loss of heterozygosity of IQGAP2 is reported in ovarian cancer (22). Hypermethylation of IQGAP2 is also observed in gastric cancer (10).…”
Section: Discussionmentioning
confidence: 98%
“…Among those altered genes, IQGAP2 is hypermethylated and its expression is decreased in ovarian cancers. Indeed, loss of heterozygosity of IQGAP2 is reported in ovarian cancer (22). Hypermethylation of IQGAP2 is also observed in gastric cancer (10).…”
Section: Discussionmentioning
confidence: 98%
“…Deletion of 19p is also a common event in many other cancers including lung cancer (13), hepatocellular carcinoma (14), and ovarian cancer (15), suggesting the existence of multiple TSGs on 19p. In esophageal cancer, chromosome 19p13.3 is a frequently deleted region.…”
Section: Introductionmentioning
confidence: 99%
“…Several expression profiling based studies have identified gene expression signatures associated with response to chemotherapy [22], [23] and to different subtypes of ovarian cancer [21], [24]. High-level amplifications of ERBB2 , MYC , PIK3CA , EVI1 , RAB25 , AKT2 , CCNE1 , NOTCH3 , FGFR2 , CCND1 , PAK1 , EMSY , ZNF217 , NCOA3 [23], [25], [26], [27], [28], [29], [30], [31], [32] and homozygous deletion, mutation, reduced expression and/or hypermethylation of TP53 , KRAS , LOT1 , DOC2 , NOEY2 , OVCA1 , SPARC , CDKN2A , RB1 , PTEN [33], [34], [35], [36], [37], [38], [39] genes have also been reported. However, little consensus or overlap between all these studies has emerged.…”
Section: Introductionmentioning
confidence: 99%